A construção rizomática do universo ficcional em António Lobo Antunes - Savegnago, Camila (2022)
This thesis has the purpose of demonstrating how the construction of the fictional universe of António Lobo Antunes resembles the open system of rhizome, as in the concept elaborated by Deleuze and Guattari (1980). More precisely, it approaches three novels of the Portuguese writer: O esplendor de Portugal (1997), Comissão das Lágrimas (2011) and Até que as Pedras se Tornem Mais leves que a Água (2017), works of different phases of Antunes’ production, but with a common theme: the colonial war, the decolonization process, the postcolonialism. The development of the study focuses mainly on the analysis of the category of the character, also approaching other elements, such as narrator, time, space. The analysis of the figuration of the main characters of these three novels evidences how they see themselves and how they are seen by others, how they build their net of personal relationships and how they are constituted by the spaces and times through which they move. Besides, as the figuration of Antunes’ characters is built mainly through memory, it is also evaluated as a powerful mechanism of legitimation or destabilization of some relations of power, reinforcing processes related to forgetting and remembering and to the overcoming (or not) of individual and collective traumas. Therefore, a reflection is made about the processes of memory and identity that come as a result of the involvement of the characters with a determined colonial context, related not only to sceneries of authoritarianism, different forms of violence, relationships of domination / exploration, but also experiences of diaspora. The rhizomatic approach allows the tracking of the multiple and heterogeneous connections among the life experiences of the characters, the figuration dispositives and a certain historical context, identifying convergences and divergences among the novels. In their connections, such narratives can be read as a big coordination capable of projecting a complex, decentered, problematizing perception of the recent history of Portugal and of the country in its postcolonial condition.